ANALYSIS OF THE ASSORTMENT POLICY OF THE TRADING ENTERPRISE AND DIRECTIONS FOR ITS IMPROVEMENT - Valentyna M. Shevchenko; Iryna V. Taranenko; Svitlana S. Yaremenko; Rustam A. Musayev (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The purpose of the article is to analyze the assortment policy of a trading company and search for directions for its improvement. The conducted analysis proved that the problems of forming an assortment policy are mostly connected with too huge assortment of goods on the market, with changes in customer needs and the growth of non-price competition. The specificity of the problem of the Ukrainian market is further complicated by the active hostilities in the country and related economic instability, inflation, low level of solvent demand, low level of population income growth, problems with the delivery of goods, etc. The essence of the concept of “assortment policy” as a field of activity of the marketing management of the enterprise is defined, which is a set of principles, the observance of which leads to the formation of an optimal assortment of goods from the point of view of increasing the competitiveness of the enterprise, taking into account its own capabilities, the capabilities of suppliers and partners, market needs, seasonality of demand, etc. Based on the ABC analysis for the “EVA” line of stores, it is emphasized that the most significant products are decorative cosmetics, perfumes for women, their share in the total turnover is on average almost 20%, they and other important products for the company belong to the category “A “, that is, they are the most important and significant, their share in the sum is 60%. The “B” group, which assumes medium significance, includes aromas, scented candles, atomizers, etc. Their share in total is 30%, it is the basis of the chain’s range of stores. The smallest share is occupied by goods of the “C” group, which are the least significant in terms of the turnover of the “EVA” line of stores: shaving products for men, cosmetic brushes, jewelry, etc. Their share in total is only 10%. An XYZ analysis was carried out for the “EVA” line of stores, the results of which show that the products marked X are products for which the demand is stable throughout the year (hygiene and care, home care products, home fragrances, etc.); products Y remain relatively stable throughout the year and products Z are volatile products, the coefficient of variation of sales volume by quarter exceeds 20% (sun protection, lip care, etc.). An integrated matrix of ABC-XYZ-analysis was built, which proves that the “EVA” store line carries out a balanced assortment policy, but does not saturate the assortment sufficiently with those items for which a higher level of profitability can be obtained, which leads to a rather low profit in recent years. For the company, the absence of product groups that can be attributed to the CZ classification, which are products of spontaneous demand, in the product range is noticeable, and therefore, increasing the product range in favor of such products can provide an opportunity to obtain a higher level of profit. It is recommended that the company continue to work on the development of new own brands and the creation of new product positions among the old ones, expanding the assortment in the “average” and “average minus” price segments.